2000
DOI: 10.1007/s005350070035
|View full text |Cite
|
Sign up to set email alerts
|

The tight junction of pancreatic exocrine cells is a morphometrically dynamic structure altered by intraductal hypertension

Abstract: The tight junction of pancreatic exocrine cells is thought to regulate paracellular permeability, and is a possible reflux route of pancreatic juice into the blood flow. Morphological changes in the tight junction of canine pancreatic acinar cells following intraductal hypertension and secretin stimulation were morphometrically analyzed to obtain evidence of the control of the paracellular reflux. Pancreatic tissues obtained from 25 dogs after intraductal hypertension, 3 dogs after secretin stimulation, and 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The tight junctions of pancreatic duct epithelial cells and exocrine cells are dynamic structures that can be disrupted by various external stimuli including ductal hypertension 18 , 19 . The disruption of pancreatic duct tight junctions is an early event in different types of pancreatitis 20 - 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The tight junctions of pancreatic duct epithelial cells and exocrine cells are dynamic structures that can be disrupted by various external stimuli including ductal hypertension 18 , 19 . The disruption of pancreatic duct tight junctions is an early event in different types of pancreatitis 20 - 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, physiological analysis revealed that patients with ulcerative colitis show decreased number of strands and defected junction barrier in inflamed colonic mucosa (Schmitz et al, ). Recently, interruptions, discontinuities, and pores of immature tight junctions were noted to play a local role in transepithelial reflux (Akao et al, ; Hashimoto et al, ) and inflammatory bowel disease (IBD; Edlblum and Turner, ). We speculate that the unique tight junction may play a role in maintaining the homeostasis of the oral regions in gerbils and possibly other desert animals, and may be part of a mechanism for survival in an extreme dry environment.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, tight junctions that are linked to the actin and microtubule cytoskeleton form a semi-permeable diffusion barrier that allows the passive diffusion of water, electrolytes and other small molecules along concentration gradients (Kikuchi et al, 2010;Matter and Balda, 2014). The tight junction, therefore, regulates paracellular fluid flow (Akao et al, 2000;Schneeberger and Lynch, 2004;Van Itallie and Anderson, 2006;G€ unzel and Yu, 2013). Several studies reported that the paracellular electric resistance or solute reflux impedance was related to the number of strands or the depth of tight junctions that varies in different cells and tissues (Mitic and Anderson, 1998;Kikuchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, dissociation of adherens junctions was present during edema formation in rat edematous pancreatitis [19]. Intraductal hypertension was shown to lead to morphological changes in tight junctions in the exocrine pancreatic cells of dogs [12]. Other claudins than claudin-1 have not been studied in the tight junction regulation in acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of acute pancreatitis, pancreatic intraductal hypertension has been shown to cause morphological changes in tight junctions in a canine model [12]. Edematous pancreatitis has been connected to dissociation of occludin and claudin-1 [13], and according to another study, edematous pancreatitis caused disruption of actin and ZO-1 linear staining [14].…”
Section: Introductionmentioning
confidence: 92%